2022
DOI: 10.1038/s41598-022-23565-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modelling of human proprioceptive sensory neurons in the neuromuscular system

Abstract: Proprioceptive sensory neurons (pSN) are an essential and undervalued part of the neuromuscular circuit. A protocol to differentiate healthy and amyotrophic lateral sclerosis (ALS) human neural stem cells (hNSC) into pSN, and their comparison with the motor neuron (MN) differentiation process from the same hNSC sources, facilitated the development of in vitro co-culture platforms. The obtained pSN spheroids cultured interact with human skeletal myocytes showing the formation of annulospiral wrapping-like struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Results demonstrated that the cells were able to interact by the formation of annulospiral wrapping-like structures. The genetic profile comparison between healthy and ALS samples pointed to lower values of ETV1 (important for motor feedback) which highlights the involvement of proprioceptive sensory neurons in this pathology (Badiola-Mateos et al, 2022). Haberts et al also developed a brain-on-achip where microchannels connected different compartments (Figure 3D).…”
Section: Figurementioning
confidence: 97%
“…Results demonstrated that the cells were able to interact by the formation of annulospiral wrapping-like structures. The genetic profile comparison between healthy and ALS samples pointed to lower values of ETV1 (important for motor feedback) which highlights the involvement of proprioceptive sensory neurons in this pathology (Badiola-Mateos et al, 2022). Haberts et al also developed a brain-on-achip where microchannels connected different compartments (Figure 3D).…”
Section: Figurementioning
confidence: 97%
“…The application of spheroid models is not limited to motor neurons but extends to proprioceptive sensory neurons as well. Researchers have utilized spheroids generated from the same human neural stem cell source to compare motor neuron spheres and proprioceptive sensory spheroids in both healthy and sporadic amyotrophic lateral sclerosis (ALS) human neural stem cells 89 . By using spheroids, one can explore the distinct characteristics and disease mechanisms of different neuronal populations relevant to IPN pathogenesis (even in a specific axon region-dependent manner), providing a more comprehensive understanding of the disease.…”
Section: Common Phenotypes?mentioning
confidence: 99%